Atividade docente na modalidade EaD : um olhar a partir do enfoque dialógico e da abordagem ergológica - Reginatto, Andréa Ad (2015)
This study discusses professors’ work activities in two Language teaching courses (Portuguese and Spanish) in the distance learning (DL) mode of a public higher education institution located in the central region of Rio Grande do Sul. The overall objective is to analyze the particularities of professors' activity on DL, considering the interface between the dialogical perspective of language and ergology in order to contribute to the knowledge/recognition of the complexity of their work. As specific objectives we delimited: i) verify, through the discursive analysis of the utterances of the DL professors, how they interact with their students, coordinators, multidisciplinary team, coworkers and tutor; (ii) verify, under the enunciative and discursive perspective, whom the professors’ activities are directed at in DL and (iii) check how the relationship between the foregoing standards and the restandardization impacts in the professors’ activities in DL. Regarding the theoretical framework, given the assumption of the dialogical constitution of language, we started from the studies developed by the Bakhtin Circle. Then, we established a dialogue with the ergological approach, which, considering the work activity as an industrious activity, make historical subjects, in the emergency of values, knowledge and experience, to face the ongoing debate between the foregoing standards and the restandardization. Concerning the methodology, we organized the study from the following steps: (i) contextualization of DL and Virtual Teaching and Learning Environment; (ii) characterization of the teaching, the professors and the students in DL mode; (iii) definition of research participants, material composition and analysis procedures, which included an interview and a semi-structured questionnaire. The instruments were applied individually to each of the three study participants (a Portuguese Language professor and two Spanish Language professors), given the theme of our research, by focusing on the relationship among the professionals and their peers and on their discourses. The results show that each professor has his/her own view on DL and, depending on the time they have been using it and their degree of involvement, the positions relating the activities performed by the participants acquire a different meaning. At times, we noticed the feeling of weariness and fatigue towards their work routine, combined with little recognition by academia peers. Thus, with this research, it is important to reiterate, through the analysis of the utterances, that the work developed by the three professors under study consists of interrelations with different partners (professors, tutors, students, multidisciplinary team, coordinations, etc.) allowing understand this collaborative work even there are different views. In this principle of collaboration, which they always act in dependence on other subjects, lies the difference between DL and the regular classroom. We understand the importance of collaborative work in professors' activities in DL courses, because therein lies the complex character of this work activity. We sought to present considerations regarding the tension of social voices and the resulting production of senses on/in the professors’ activities in DL, contributing not only to the theoretical and methodological development of researches that address the interface language and work, but also to the reflection of the complex DL professors’ activities. We understand that teaching in this mode requires from professors, besides all predetermined requirements of their occupation, the task of acting in a context for which they were not prepared to. This shows the importance of creating a space where these professionals can be heard and also talk about the concerns surrounding their work routine, which goes beyond preparing and running classes.